Chemo-enzymatic synthesis of new resveratrol-related dimers containing the benzo[b]furan framework and evaluation of their radical scavenger activities. Issue 20 (20th May 2015) - Beneventi, Elisa; Conte, Silvia; Cramarossa, Maria Rita; Riva, Sergio; Forti, Luca
Abstract: The chemo-enzymatic synthesis and the evaluation of radical scavenger performance of resveratrol-related dimers with antioxidative power have been investigated. The dimeric compounds, containing the benzo[ b ]furan framework, were prepared via an oxidative dimerization catalyzed by a laccase from Trametes versicolor, followed by a treatment with the organic oxidant DDQ. This methodology can be useful for the synthesis of various 2, 3-diarylbenzo[ b ]furans derivates, a class of compound that exhibits a wide range of biological activities. Graphical abstract: